Sustainability Tourism Industry Development: A Strategic Stakeholder Approach Analysis - Assagaf, Aminullah; Muhammad, Zikri; Salmiay, Taty; Renreng, Mulhayati; Taufiq Possumah, Bayu (International Journal of Engineering and Technology, 2018)
The tourism industry development sustainability is represented in how the all resources managed in such a manner to fulfill the requirement of economics, social and environmental towards integrated social cultural systems. Stakeholder approach is one way to achieve the sustainability industry development. It is an approach that emphasizing role and involvement of stakeholder in the context of opportunity access in managing the industry of tourism, with nobleness of political culmination, democratic, fair profit sharing for the local communities in tourism activities
Keywords: Sustainability; Tourism; Stakeholder.